Long-Term Treatment with Empagliflozin Attenuates Renal Damage in Obese Zucker Rat - Manne, Nandini D. P. K.; Ginjupalli, Gautam Kumar; Rice, Kevin M.; Arvapalli, Ravikumar; Graffeo, Vincent A.; Bandarupalli, Venkata V. K.; Blough, Eric R. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Introduction Empagliflozin, a known inhibitor of sodium-glucose cotransporter type 2 (SGLT2) decreases glucose reabsorption by the renal tubules and promotes glucose excretion into the urine. While the effectiveness of Empagliflozin in the management of hyperglycemia along with associated cardiovascular and all-cause mortality has been demonstrated previously, the therapeutic benefits associated with the long-term use of this drug in obese animals have yet to be investigated.Methods Male 5-week-old lean and obese Zucker rats were randomly assigned to one of the 4 groups- lean control, lean treated, obese control, obese treated and treated with either Empagliflozin (10 mg/kg BW / day) or placebo for 25 weeks to investigate the therapeutic effect of Empagliflozin.Results Empagliflozin treatment in the obese animals was associated with decreased body weight, attenuated the loss of F-actin from the renal tubules and improved renal structure and function. These changes in renal function were associated with significant improvements in the glucose tolerance, and decreased non-fasting circulatory levels of glucose, amylase, and other inflammatory markers including NGAL, cystatin C, and clusterin.Conclusion Long-term use of Empagliflozin in diabetic obese Zucker rats is associated with improvements in glucose tolerance and decreased loss of renal structure and function.
Keywords: SGLT2 inhibitor; type 2 diabetes; glucose tolerance; inflammation